SEBUAH STUDI KASUS KELUARGA PADA ANAK DENGAN TRIGER SUARA KERAS: MENGGUNAKAN SYSTEMATIC DESENSITIZATION (SD) - Elviana Rohmah Rosyidatul ‘Ula; Aradhana Maheswara; Shiva Nur Aisyah; Taqiyyatul Azizah; Shabrina Nailah Lubis; Devi Ratnasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research explores the therapy process for a young child who suffers from severe anxiety towards loud noises, a result of previous family trauma. The goal of this study is to assess how effective systematic desensitization is in minimizing the child's fearful reactions and enhancing their everyday activities. A qualitative case study approach was utilized, gathering information through interviews, behavioral assessments, and records collected over five counseling sessions. The intervention incorporated organized phases that involved relaxation exercises, gradual exposure to sound, and reinforcement of healthy coping strategies. Results show that at the beginning, the child exhibited significant physical and emotional reactions such as flinching, avoidance, and ongoing anxiety about future sounds. Following the gradual implementation of systematic desensitization, the child showed improved tolerance for different sounds, less avoidance, and better management of their emotions. Educators and caregivers also noted positive changes in the child's involvement in classroom activities and social interactions. This study concludes that systematic desensitization effectively addresses trauma associated with sound in children, especially when there is strong communication support between family and school. The findings emphasize the necessity of early intervention, a consistent approach to exposure, and a teamwork atmosphere to enhance therapeutic outcomes and mitigate long-lasting psychological effects.